Digital Transformation of Waqf Management: Innovation Pathways and Policy Directions in Muslim-Majority Developing Countries - Riduwan; Erwan Aristyanto (Universitas Islam Negeri Kiai Ageng Muhammad Besari Ponorogo, 2025)
Waqf represents a powerful economic instrument with substantial potential to empower communities, particularly in countries with large Muslim populations. In the digital era, innovations in the management of productive waqf offer new opportunities to enhance the effectiveness and efficiency of waqf fund utilization. This study aims to explore innovative models of productive waqf management and their impact on community economic empowerment. Employing a qualitative descriptive approach, this research conducts a comprehensive literature review of journal articles, books, and other relevant sources to analyze digital waqf practices in developing countries. The findings reveal that digital innovations—such as crowdfunding platforms, blockchain technology, and mobile applications—can significantly improve the efficiency, accountability, and outreach of waqf management. These technologies hold substantial potential to expand waqf fundraising, enhance transparency, and facilitate greater public participation. Nevertheless, several challenges persist, including low digital literacy, limited public trust in digital waqf systems, and the need to align regulatory frameworks with technological developments. This study offers insights and recommendations for policymakers and practitioners, particularly in Indonesia, to harness digital waqf innovations in supporting sustainable development and advancing community empowerment. Abstrak Wakaf merupakan instrumen ekonomi yang kuat dengan potensi signifikan untuk memberdayakan masyarakat, terutama di negara-negara dengan populasi Muslim yang besar. Di era digital, inovasi dalam pengelolaan wakaf produktif menghadirkan peluang untuk meningkatkan efektivitas dan efisiensi pemanfaatan dana wakaf. Penelitian ini bertujuan untuk mengeksplorasi model-model inovatif pengelolaan wakaf produktif dan dampaknya terhadap pemberdayaan ekonomi masyarakat. Penelitian ini menggunakan metode deskriptif kulalitatif dengan teknik tinjauan pustaka yang komprehensif dari artikel jurnal, buku, dan sumber-sumber relevan untuk menganalisis praktik wakaf digital di negara-negara berkembang. Temuan penelitian menunjukkan bahwa inovasi digital seperti platform crowdfunding, teknologi blockchain, dan aplikasi seluler dapat secara signifikan meningkatkan efisiensi, akuntabilitas, dan jangkauan pengelolaan wakaf. Teknologi-teknologi ini menawarkan potensi untuk memperluas penghimpunan dana wakaf, meningkatkan transparansi, dan memfasilitasi partisipasi publik yang lebih besar. Namun, masih terdapat tantangan, termasuk rendahnya literasi digital, terbatasnya kepercayaan publik terhadap sistem wakaf digital, dan perlunya menyelaraskan kerangka regulasi dengan perkembangan teknologi. Penelitian ini memberikan wawasan dan rekomendasi bagi para pembuat kebijakan dan praktisi, khususnya di Indonesia, dalam memanfaatkan inovasi wakaf digital untuk mendukung pembangunan berkelanjutan dan memberdayakan masyarakat.